2021
DOI: 10.22541/au.162679471.13672315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term responses of benthic invertebrates to rotenone treatment

Abstract: Biological invasions are regarded as one of the largest threats to native biodiversity. The eradication of non-native parasites by culling of hosts are a controversial conservation strategy, particularly when using indiscriminate methods involving whole ecosystem collateral damage. While short-term effects are abundantly documented, long-term surveys are needed to detect potential wider ecosystem effects. Here, we report a six-year study on effects of the piscicide rotenone on invertebrate communities from a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The chemical treatments in the rivers also kill much of the benthic fauna, including gill-breathing insect larvae (Kjaerstad & Arnekleiv, 2011). However, studies have shown that most of the invertebrate fauna reestablish within a year or so, and common species quicker than rare species (Kjaerstad et al, 2016;Kjaerstad et al, 2021). As only the anadromous part of the rivers is treated, the re-establishment of invertebrates is mostly due to drifting from the areas upstream of the salmon migration barrier (Kjaerstad et al, 2021).…”
Section: Re-e S Tab Lis Hments Of Fis H and Inverteb R Ate S Af Ter C...mentioning
confidence: 99%
“…The chemical treatments in the rivers also kill much of the benthic fauna, including gill-breathing insect larvae (Kjaerstad & Arnekleiv, 2011). However, studies have shown that most of the invertebrate fauna reestablish within a year or so, and common species quicker than rare species (Kjaerstad et al, 2016;Kjaerstad et al, 2021). As only the anadromous part of the rivers is treated, the re-establishment of invertebrates is mostly due to drifting from the areas upstream of the salmon migration barrier (Kjaerstad et al, 2021).…”
Section: Re-e S Tab Lis Hments Of Fis H and Inverteb R Ate S Af Ter C...mentioning
confidence: 99%
“…Studies on benthic invertebrates in rotenone treated rivers suggest short term impacts, with increasing effects at higher water temperatures and rotenone concentrations, and longer exposure times. Although most invertebrate taxa recolonize within a year (Kjaerstad et al 2021), recolonization can take several years if the rotenone treatment comprised most of the basin (Mangum and Madrigal 1999).…”
Section: Case Study 2: Eradicating Gyrodactylus Salaris From Norwegia...mentioning
confidence: 99%
“…Three key aspects are evident from the studies presented within the special issue. First, long term studies (e.g., Bedmar et al, 2022; Guareschi et al, 2022; Kjærstad et al, 2022), are imperative within the field of invasion biology. Without such studies, understanding the temporal trajectories of invasion dynamics and factors influencing establishment may dictate that monitoring efforts are too short‐sighted to be effective (Christie et al, 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…As with most chemical control methods, application is extremely controversial, but long-term studies examining the ecological consequences are limited. Kjaerstad, Arnekleiv, Velle, and Finstad (2022) documented benthic macroinvertebrate's short (<1 month) and long term (4+ years) responses to rotenone treatment in a Norwegian watercourse. Although the effects were relatively minor (assessed via temporal beta-diversity), their findings stress the importance of exposure duration with severe effects occurring up to 8 months after treatment following a long-term low dose.…”
Section: Monitoring and Managing The Spread Of Innsmentioning
confidence: 99%